Corporate Governance and Firm Value: Empirical Evidence in Malaysia - Tan, Mabel Yunn Ru (2009)
Well governed firms have been noted to have higher firm performance. However, this is still an empirical question in the context of Malaysia. This paper aims to examine the effect of corporate governance practices on firm value among 151 public listed companies on Bursa Malaysia Main Board between 2006 and 2008. We use the overall governance practice scores (CGS) to measure the level of compliance carried out by the sample firms. The results find that better corporate governance is highly correlated with better price to book ratio but not significantly associated with Tobin’s Q and return on asset. It is clear that corporate governance compliance does influence firm value in Malaysia even though the effect may not be strong. Additionally, we also find that firms with higher leverage lead to weaker performance while greater capital expenditure contributes to better firm performance. There are two direct insights to policy makers and practitioners follow from our analysis. First, to see the effectiveness of corporate governance on firm value, companies should be given incentives to move from mere compliance to truly instilling corporate governance into the culture of corporation; and second, our CGS measure of governance practices gives investor a quantitative tool to better assess Malaysian firms.